2008
DOI: 10.1172/jci33800
|View full text |Cite
|
Sign up to set email alerts
|

Prostacyclin primes pregnant human myometrium for an enhanced contractile response in parturition

Abstract: An incomplete understanding of the molecular events that regulate the myometrial transition from the quiescent pregnant state to the active contractile state during labor has hindered the development of improved therapies for preterm labor. During myometrial activation, proteins that prime the smooth muscle for contraction are upregulated, allowing maximal responsiveness to contractile agonists and thereby producing strong phasic contractions. Upregulation of one such protein, COX-2, generates PGs that induce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 65 publications
2
41
0
Order By: Relevance
“…Given the pleiotropic nature of such cAMP-mediated regulation, one wonders whether other receptor-coupled stimuli (e.g., β-adrenergic agonists, prostaglandin E2, etc.) or pharmacological agents (e.g., forskolin) will elicit the same outcomes as outlined here by Fetalvero et al (4). Similarly, the expression of a wide variety of proteins would be expected to be changed by procedures that raise cAMP, not just the few focused on in the current study.…”
Section: Prostacyclin Signaling Via Camp and Pkamentioning
confidence: 56%
See 2 more Smart Citations
“…Given the pleiotropic nature of such cAMP-mediated regulation, one wonders whether other receptor-coupled stimuli (e.g., β-adrenergic agonists, prostaglandin E2, etc.) or pharmacological agents (e.g., forskolin) will elicit the same outcomes as outlined here by Fetalvero et al (4). Similarly, the expression of a wide variety of proteins would be expected to be changed by procedures that raise cAMP, not just the few focused on in the current study.…”
Section: Prostacyclin Signaling Via Camp and Pkamentioning
confidence: 56%
“…Based on the data presented in their study, Fetalvero et al (4) speculate that that their observations have important implications with respect to our understanding of myometrial activation, and hence clinical trials of prostacyclin-based therapeutics in pregnancy are warranted because they may lead to better strategies to induce labor or prevent preterm labor (PTL). PTL is the most serious pregnancy complication in developed countries and an important precedent of chronic disability.…”
Section: Clinical Relevance Of the New Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Although PGF2a dose-dependently increased the uterine activation proteins, including CX43 (Xu et al 2013), the most highly expressed prostaglandin in human myometrium is PGI2 (Omini et al 1979), which is normally known as a smooth muscle relaxant (Taggart et al 2008). In the pregnant human myometrium at term, however, PGI2 mediates upregulation of CX43 and contractile proteins such as SM-MHC and a-SMA via activating PKA in human myometrial cells in vitro, resulting in an enhanced contractile response to oxytocin (Fetalvero et al 2008).…”
Section: Connexin Involvement In Labourmentioning
confidence: 99%
“…Research with women or using animal models has shown that prolonged administration of progesterone is able to prevent preterm birth (Norman et al 2011). Progesterone probably acts as an antiinflammatory hormone and prevents prostacyclin activation (Fetalvero et al 2008). Interfering with prostaglandin synthesis as a therapeutic treatment to arrest myometrial contraction was considered to be a promising approach, but there is little evidence that COX2 inhibitors could prevent preterm labour as shown by a recent Cochrane study (Khanprakob et al 2012).…”
Section: Implicating Connexins In Birth Complicationsmentioning
confidence: 99%